Application of seaweed (Kappaphycus alvarezii) in Malaysian food products - Mohammad, Salma Malihah; Mohd Razali, Siti Farhanah; Mohamad Rozaiman, Nur Hdayah Nabilah; Laizani, Athiah Nabihah; Zawawi, Norhasnida (Universiti Putra Malaysia, 2019)
Kappaphycus alvarezii is a species of red algae, and one of the most important carrageenan sources for food, cosmetic, and pharmaceutical industries. It is commercially cultivated in the eastern part of Malaysia. Although K. alvarezii is rich in nutrients, it is limited in its integration into Malaysian food products. Therefore, the present work was conducted to investigate the quality characteristics, sensorial attributes, and antioxidant activity of K. alvarezii in Malaysian food products. Seaweed puree (SP) from K. alvarezii at 10%, 20% and 30% concentrations were prepared in the formulations of fish sausages, flat rice noodles and yellow alkaline noodles. Proximate analysis, physicochemical analysis, microbial count, total phenolic content (TPC), sensory evaluation, and consumer acceptance survey of the formulated food were conducted. The incorporation of K. alvarezii significantly increased the fibre, moisture, and ash content in formulated foods. In addition, the TPC content of K. alvarezii food also significantly increased up to 42 mg GAE/100 g. The presence of SP in food at higher concentration decreased the microbial counts. Sensory analysis confirmed that only fish sausages added with SP was overall acceptable as compared to control. Based on customer survey, functional foods that are “research proven” were the most preferred. In conclusion, K. alvarezii has the potential to be incorporated in Malaysian food products and developed as functional food.